Pengaruh Lingkungan Kerja Terhadap Komitmen Organisasional dengan Kepuasan Kerja sebagai Variabel Mediasi di Dinas Lingkungan Hidup di Kabupaten Soppeng - Nur Alfiani Riah; Tenri S.P Dipoatmodjo; Rezky Amalia Hamka; Burhanuddin; Uhud Darmawan Natsir (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the influence of the work environment on organizational commitment, with job satisfaction as a mediating variable, among employees of the Soppeng Regency Environmental Service. This study used a quantitative method with an associative approach. The population in this study was all 43 employees of the Soppeng Regency Environmental Service, who also served as the sample using a saturated sampling technique. Data were collected through questionnaires, interviews, observations, and documentation, then analyzed using regression analysis, t-tests, F-tests, and mediation tests (Sobel). The results indicate that the work environment has a positive and significant effect on job satisfaction and organizational commitment. Employees who work in a comfortable, safe environment supported by harmonious working relationships tend to have higher work enthusiasm and loyalty to the organization. Furthermore, job satisfaction also has a positive and significant effect on organizational commitment, where employees who are satisfied with their jobs demonstrate greater loyalty, responsibility, and commitment to remaining with the organization. This study also found that job satisfaction significantly mediates the effect of the work environment on organizational commitment, thus serving as a partial mediator in this relationship. These findings confirm that improving the work environment not only directly impacts employee commitment but also indirectly through increased job satisfaction.